The Inconsistence Of Laws In The Registration Of Land Rights Transfer In Order Of Tax Amnesty - Angelica Saulina Hutapea (Faculty of Law, University of Mataram, 2018)
The writing of this journal discusses legal issues related to legislation inconsistencies concerning registration of land rights transfer which related to tax amnesty. In accordance with Article 37 of Government Regulation No. 24 of 1997 that only recognizes land rights transfer trough trade, exchange, grant, inbreng, and other legal act of rights transfer, but with the existence of Perkaban No. 15/2017, it states that the registration of land rights transfer can be based on the nominee agreement. The objective of this journal is to analyze the implications of legislation inconsistencies concerning registration of land rights transfer which related to tax amnesty and the validity of nominee agreement based on Indonesian law. The research method used is normative juridical with legislation approach and conceptual approach. The discussion result of this journal is the authorization of nominee agreement usage in terms of registration of land rights transfer, but only in the case of tax amnesty, refers to the interpretation of Article 1337 of Civil Code which states that if the things that are prohibited set forth in the law then the thing in question is allowed.